Is a test of cure necessary following treatment for cervical infection with Chlamydia trachomatis?. Issue 6 (December 1990) - Radcliffe, K W; Rowen, D; Mercey, D E; Mumtaz, G; Ridgway, G L; Robinson, A J; Bingham, J S
Abstract : Tests of cure (TOC) were performed on specimens from 106 women following treatment for chlamydial infection of the cervix. 91 women attended for the first TOC with enzyme immunoassay (EIA) within one week of finishing antibiotics. Three were EIA positive, 88 were EIA negative. These three women were subsequently EIA and culture negative although they received no further antibiotics. Ninety women returned for the second TOC with EIA and culture between seven and 27 days after completing treatment. All the results were negative. Routine TOC is unnecessary following appropriate antichlamydial therapy. If TOC is indicated antigen-detection methods should not be used immediately after finishing antibiotics as misleading positive results may be obtained. EIA or culture at one week or later after treatment is reliable.